Improved singlet oxygen generation of axially ruthenium(II) complex substituted silicon(IV) phthalocyanine by sono-photochemical studies - Atmaca, Goknur Yasa; Elmali, Fikriye Tuncel; Erdogmus, Ali (ELSEVIER, 2023)
Sono-photodynamic study, which shows an exceedingly high therapeutic outcome compared to photodynamic study, is a new alternative method for the anticancer treatments. However there are not enough related studies in the literature. Therefore, this study initially aimed to design and synthesize ruthenium (II) complex substituted silicon phthalocyanine for a suitable sono-photosensitizer and then to increase singlet oxygen production using sono-photochemical studies. The results showed that the substituent group improved the generation of singlet oxygen quantum yield of silicon (IV) phthalocyanine dichloride, and also the sono-photochemical method increased the yield approximately two times ( CIA= 0.38 in photochemical study, 0.66 in sono-photochemical study). This article will pave the way for studies that seek to improve sono-photochemical properties.
Keywords: Sono-photodynamic therapy; Silicon phthalocyanine; Photodynamic therapy; Singlet oxygen; Ruthenium complex; POLYPYRIDYL COMPLEXES; IN-VITRO; CANCER; ZINC; Chemistry